2003
DOI: 10.1002/ejoc.200200673
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Four Stereoisomers of 1‐Amino‐2‐(hydroxymethyl)cyclobutanecarboxylic Acid and Their Biological Evaluation as Ligands for the Glycine Binding Site of the NMDA Receptor

Abstract: A synthesis of all four stereoisomers [(1S,2S)‐, (1R,2R)‐, (1S,2R)‐, (1R,2S)‐] of 1‐amino‐2‐(hydroxymethyl)cyclobutanecarboxyclic acid is presented. The synthesis is based on the chiral glycine equivalent 1, employed in both enantiomeric forms. The key step involves the cyclization of the silyl‐protected iodohydrins 5a−d to the corresponding spiro derivatives 6a−d with the aid of the phosphazenic base tBu‐P4. The final compounds were found to display moderate potency as ligands for the glycine binding site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Wanner et al 148 reported the synthesis of all four stereoisomers of 1-amino-2-(hydroxymethyl)-cyclobutanecarboxylic acid (1 S ,2 S )- and (1 R ,2 R )- 13f , (1 S ,2 R )- and (1 R ,2 S )- 14f through a double alkylation of the chiral glycine equivalent ( R )- 173 . In this context, reaction of ( R )- 173 with s -BuLi in THF at −78 °C, followed by addition of but-3-enyl triflate, afforded the alkylated products 249a and 249b in 69% yield and 95.5:4.5 dr.…”
Section: Synthesis Of 1-aminocycloalkanecarboxylic Acidsmentioning
confidence: 99%
“…Wanner et al 148 reported the synthesis of all four stereoisomers of 1-amino-2-(hydroxymethyl)-cyclobutanecarboxylic acid (1 S ,2 S )- and (1 R ,2 R )- 13f , (1 S ,2 R )- and (1 R ,2 S )- 14f through a double alkylation of the chiral glycine equivalent ( R )- 173 . In this context, reaction of ( R )- 173 with s -BuLi in THF at −78 °C, followed by addition of but-3-enyl triflate, afforded the alkylated products 249a and 249b in 69% yield and 95.5:4.5 dr.…”
Section: Synthesis Of 1-aminocycloalkanecarboxylic Acidsmentioning
confidence: 99%
“…14 16 and later by Fadel et al 17 Wanner and co-workers described the use of a chiral glycine equivalent and a strategy based on a cyclization reaction to obtain the four stereoisomers of 1-amino-2-(hydroxymethyl)-cyclobutane carboxylic acid. 18 Our experience on different approaches to analogues of phenylalanine c n Phe highlighted the classic Strecker reaction as a useful method. Indeed, we reported an efficient synthesis of trans-c 6 Phe through a completely diastereoselective Strecker reaction.…”
Section: Resultsmentioning
confidence: 99%
“…isopropyl group are the most frequent substituents (10 structures). Compounds (1) and (2), and the four structures with CSD refcodes GUYNIX (Koch et al, 2003a), JAHBOK and JAHBUQ (Małecka et al, 2003), and OHOXAK (two molecules; Koch et al, 2003b), possess a methoxy group at the C5 atom, and methyl and tert-butyl substituents at the C6 atom. The overlapping of these molecules and compounds (1) and(2) is presented in Fig.…”
Section: Figurementioning
confidence: 99%